2004
DOI: 10.1016/j.jhealeco.2003.10.003
|View full text |Cite
|
Sign up to set email alerts
|

An economic analysis of adult obesity: results from the Behavioral Risk Factor Surveillance System

Abstract: This paper examines the factors that may be responsible for the 50% increase in the number of obese adults in the US since the late 1970s. We employ the 1984-1999 Behavioral Risk Factor Surveillance System, augmented with state level measures pertaining to the per capita number of fast-food and full-service restaurants, the prices of a meal in each type of restaurant, food consumed at home, cigarettes, and alcohol, and clean indoor air laws. Our main results are that these variables have the expected effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
506
5
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 853 publications
(552 citation statements)
references
References 28 publications
28
506
5
13
Order By: Relevance
“…Speculatively, the bias usually found in self-reported measurements might have been reduced in the NHANES due to knowledge about the upcoming physical exam. It also suggests that adjusting self-reports in other datasets using the difference between self-reports and measured height and weight in the NHANES is not valid (performed, for instance, in [39,40]). More generally, exploring differences in self-reported and measured BMI by race/ethnicity and SES would be an interesting topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Speculatively, the bias usually found in self-reported measurements might have been reduced in the NHANES due to knowledge about the upcoming physical exam. It also suggests that adjusting self-reports in other datasets using the difference between self-reports and measured height and weight in the NHANES is not valid (performed, for instance, in [39,40]). More generally, exploring differences in self-reported and measured BMI by race/ethnicity and SES would be an interesting topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason might be having less time available for food preparation and consequently eating ''fast food.' ' Chou et al (2004) examined the relationship between relative price levels and BMI. They investigated the effects of the price of a meal in fast food restaurants, the price of food consumed at home, and the price of cigarettes on BMI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…That is, technological change has contributed to the rise in obesity either by lowering the cost of consuming calories and/or by raising the cost of expending them (Philipson and Posner 2003). In addition, the prevalence of fast-food restaurants, higher prices of alcohol and cigarettes (Chou et al 2004), lower time costs of food preparation resulting from technological changes in mass food preparation (Cutler et al 2003) and even the rise of sprawl patterns in land development (Plantinga and Bernell 2007;Ewing et al 2003) have been linked to rising obesity. In a cross-country comparison among OECD countries, Loureiro and Nayga (2005) showed that the percentage of female labor force participation positively affects obesity rates.…”
Section: Literature Reviewmentioning
confidence: 99%